2016
DOI: 10.1371/journal.pone.0148913
|View full text |Cite
|
Sign up to set email alerts
|

Further We Travel the Faster We Go

Abstract: The average travelling speed increases in a nontrivial manner with the travel distance. This leads to scaling-like relations on quite extended spatial scales, for all mobility modes taken together and also for a given mobility mode in part. We offer a wide range of experimental results, investigating and quantifying this universal effect and its measurable causes. The increasing travelling speed with the travel distance arises from the combined effects of: choosing the most appropriate travelling mode; the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…In general, a trip can consist of multiple connections and may in fact be multimodal (multiple components of travel) with the corresponding waiting-time distributions associated with the modes of transportation [102]. Also, it is observed that the apparent speed v increases with travel distance according to the following power-law functional form [101] v ∼ r β ,…”
Section: Physics Of Mobility 321 Distance Travel Time and Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, a trip can consist of multiple connections and may in fact be multimodal (multiple components of travel) with the corresponding waiting-time distributions associated with the modes of transportation [102]. Also, it is observed that the apparent speed v increases with travel distance according to the following power-law functional form [101] v ∼ r β ,…”
Section: Physics Of Mobility 321 Distance Travel Time and Effectmentioning
confidence: 99%
“…The orange dashed lines represents the best fit to | v | ∝ √ t which corresponds to a Brownian acceleration model. Figure from [103].from which the relation v ∼ √ r directly follows[101].…”
mentioning
confidence: 99%
“…Longer trips are typically taken on fast trains or planes with a small number of stops. The relation between distance and travel time is therefore not simple [12]: it has been shown that the effective speed increases with the travel distance as a square root [51], owing to the hierarchical structure of transportation systems [52] (Fig. 2).…”
Section: Mobilitymentioning
confidence: 99%
“…Recently our group revealed an interesting dynamical scaling between travel time and travel distance (measured along the geodesic lines), holding on ten orders of spatial magnitudes for human traveling modes 18 . The coarse-grained result is that the estimated average travel time scales roughly proportionally with the square root of the travel distance.…”
Section: Introductionmentioning
confidence: 99%